Writing about the Personal Utility of Learning Contents in a Learning Journal Improves Learning Motivation and Comprehension. (19th December 2012) - Schmidt, Kristin; Maier, Julia; Nückles, Matthias
Abstract : Reflecting on the personal utility and value of learning contents is important for motivation building and engagement in high quality learning processes. We investigated the effects of a personal-utility prompt in journal writing on students' learning motivation and comprehension in biology education. 40 students of a German secondary school took part in a quasi-experimental field study. The students kept a weekly learning journal over six weeks. For writing their journal entries, the students received a brief instruction that either did or did not include a personal-utility prompt. Results showed that the personal-utility prompt successfully supported the students in reflecting about the personal utility of the learning contents. Consequently, students in the personal-utility prompt condition reported higher degrees of learning motivation and achieved better comprehension scores as compared to students who had no personal-utility prompt available. Evidently, using journal writing to reflect upon the utility and value of learning contents is a beneficial method to support students' learning motivation and comprehension in secondary science education.